2023
DOI: 10.1039/d2ra06033g
|View full text |Cite
|
Sign up to set email alerts
|

DES: their effect on lignin and recycling performance

Abstract: Deep eutectic solvents (DES) are the most common method for pre-treating lignocellulose in the extraction and degradation of lignin. The development and application of efficient methods of DES recovery can significantly reduce the cost of biomass refining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…246,249 Ultimately, the residual content of β-O-4′ linkages and the degree of condensation of the isolated lignin depend on the properties of the solvent and the operating temperature. 249–252…”
Section: Lignocellulose Pretreatment As a Source Of Ligninmentioning
confidence: 99%
“…246,249 Ultimately, the residual content of β-O-4′ linkages and the degree of condensation of the isolated lignin depend on the properties of the solvent and the operating temperature. 249–252…”
Section: Lignocellulose Pretreatment As a Source Of Ligninmentioning
confidence: 99%
“…The Vienna ab initio simulation package (VASP) was used for all spin-polarized density functional theory (DFT) calculations. 20,21 The revised Perdew-Burke-Ernzerhof (RPBE) functional was employed to model the electronic exchange and correlations, while the Tkatchenko-Scheffler (TS) method was used to consider the dispersion correction with specied parameters. 22,23 The projector-augmented wave (PAW) method was employed to describe the electron-ion interactions.…”
Section: Number Of Electrons Calculationmentioning
confidence: 99%
“…11 Through PDMS-based soft lithography technology, combined with PDMS surface treatment for multilayer bonding, 12 3D chip fabrication can be realized, and microfluidic chips that meet different structural and functional requirements can be fabricated. [13][14][15] At the same time, making full use of the advantages of micromachining, the room-temperature liquid metal (LM, such as gallium-based alloy) is directly injected into the microchannel to form electrodes, [16][17][18][19] which greatly reduces the complexity of electrode fabrication compared with traditional processes such as sputtering, combined with other advantages, such as high flexibility, deformability, electrical conductivity, thermal conductivity and nontoxicity. [20][21][22][23] In addition, a study has shown that the reversible bonding process of polycarbonate (PC) and PDMS can be used to fabricate complex blind ends and contact liquid metal microelectrodes.…”
Section: Introductionmentioning
confidence: 99%